1982
DOI: 10.1002/j.2050-0416.1982.tb04067.x
|View full text |Cite
|
Sign up to set email alerts
|

Esterases of Baker's Yeast. Ii. Substrate Specificities Towards Esters Formed During Sugar Fermentations

Abstract: Ethyl esters of fatty acids (C,-C,,), isoamyl acetate and 2-phenethyl acetate were studied as sub strates for yeast esterases and compared with the synthetic substrates, p-nitrophenyl esters and P-naphthyl esters. Intact yeast, the 55% and 55-75% ammonium sulphate precipitate of centrifuged yeast homogenate, and partly purified esterases were used for the determination of the hydrolysation activity towards the esters.The results showed that the yeast esterases prefer to hydrolyse the ethyl esters with acyl cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…The highest catalytic activity was found with β-naphthyl acetate, whereas no hydrolytic activity was detectable with esters of fatty acids longer than C14 (data not shown), confirming previously reported results 19 . The sub-cellular localization of the enzyme/s with esterase activity was then investigated and a method for their visualization on electrophoretic gels was developed.…”
Section: )79087 %2( (-7'977-32supporting
confidence: 92%
See 1 more Smart Citation
“…The highest catalytic activity was found with β-naphthyl acetate, whereas no hydrolytic activity was detectable with esters of fatty acids longer than C14 (data not shown), confirming previously reported results 19 . The sub-cellular localization of the enzyme/s with esterase activity was then investigated and a method for their visualization on electrophoretic gels was developed.…”
Section: )79087 %2( (-7'977-32supporting
confidence: 92%
“…From this point of view, the characterization of the different yeast esterases is of primary importance and the methods described here for the fractionation and visualization on gels of these enzymes contribute to a better understanding of their action. However, the esters used in this study are rather unspecific substrates for several forms of esterases and it must be stressed that the affinity of the various esterases for a given substrate can be very different 19 . Therefore, in order to elucidate the effects of these enzymes on ester levels, it will be necessary to test their activities on those substrates that are actually found in wine.…”
Section: (Ixigxmsr Sj Iwxivewi Egxmzmx] Sr Ipigxvs Tlsvixmg Kipwmentioning
confidence: 99%
“…As esterases are responsible for the breakdown of esters, it is clear that their activity may affect the concentration of certain volatile esters. In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70).…”
Section: Discussionmentioning
confidence: 99%
“…The esterase found in the present study has a broad substrate preference towards esters of p-nitrophenol, but only hydrolyses the long-chain esters, ethyl hexanoate and ethyl octanoate in beer. A broad substrate specificity was also observed for the cell wall esterases and intracellular esterases (Schermers et al, 1976;Parkkinen and Suomalainen, 1982). The esterase described here is relatively resistant to heat; after pasteurization, where heating at 60 C for 20 min is performed, a low level of esterase activity was still present.…”
Section: Discussionmentioning
confidence: 53%